Different antibiotic protocols in the treatment of severe chronic periodontitis: A 1‐year randomized trial. (26th July 2017) - Borges, Ivan; Faveri, Marcelo; Figueiredo, Luciene Cristina; Duarte, Poliana Mendes; Retamal‐Valdes, Belén; Montenegro, Sheyla Christinne Lira; Feres, Magda
Abstract: Aim: To evaluate the clinical effects of different dosages of metronidazole (MTZ) and durations of MTZ + amoxicillin (AMX) in the treatment of generalized chronic periodontitis (GChP). Material and Methods: Subjects with severe GChP were randomly assigned to receive scaling and root planing (SRP)‐only, or combined with 250 or 400 mg of MTZ + AMX (500 mg) thrice a day (TID), for 7 or 14 days. Subjects were monitored for 1 year. Results: One hundred and nine subjects were enrolled. At 1 year, 61.9% and 63.6% of the subjects receiving AMX + 250 or 400 mg of MTZ for 14 days, respectively, reached the clinical endpoint for treatment (≤4 sites with probing depth ≥5 mm), against 31.8% of those taking 250 or 400 mg of MTZ for 7 days ( p < .05) and 13.6% of those receiving SRP‐only ( p < .05). Fourteen days of MTZ + AMX was the only significant predictor of subjects reaching the clinical endpoint at 1 year (OR, 5.26; 95% CI, 2.3–12.1, p = .0000). The frequency of adverse events did not differ among treatment groups ( p > .05). Conclusion: The adjunctive use of 400 or 250 mg of MTZ plus 500 mg of AMX/TID/14 days offers statistically significant and clinically relevant benefits over those achieved with SRP alone in the treatment of severe GChP. The added benefits of the 7‐days regimen in this population were less evident. (ClinicalTrials.gov NCT02735395).